Proportion of Birth Asphyxia and Its Associated Factors among Newborns Delivered in Public Hospitals in Addis Ababa, Ethiopia, 2019: A Multicenter Cross-Sectional Study - Godie, Yohannes; Yenus, Hedija; Ayenew, Fentahun; Birhanu, Dires; Guadie, Yitayal (Journal of Maternal and Child Health, 2022)
Background: Birth asphyxia is a serious clinical problem that causes neonatal mortality and morbidity worldwide, Even though Ethiopia has made significant progress in lowering the under-five mortality rate, the neonatal mortality burden has not decreased significantly, which may be due to birth asphyxia. Therefore, the purpose of this study was to address this gap by assessing the prevalence of neonatal asphyxia and its associated factors among newborns in Addis Ababa public hospitals, Ethiopia. Subjects and Method: A facility-based cross-sectional study was conducted on 683 live newborns born at Addis Ababa public hospitals. Data were gathered through structured face-to-face interviews, questionnaire administration, and a systematic random sampling technique with proportional allocation. For statistical analysis, data were entered into Epi-data version 4.6 and exported to SPSS version 26. All variables with p-value ≤ 0.2 were taken into the multivariable model. A statistical significant level was declared at 95% CI and adjusted odds ratio (AOR) at a p <0.05. Results: The prevalence of birth asphyxia was 72 (10.6%) with a 95 % CI of (8.3 to 13.0). According to this study, birth asphyxia was significantly associated with the odds of newborns whose mothers were not educated (AOR= 8.09; 95 % CI= 1.63 to 40.19; p= 0.011), prolonged labor (AOR= 3.52; 95 % CI= 1.47 to 8.43; p= 0.005), ante-partum hemorrhage (AOR= 5.36, 95 % CI= 1.69 to 16.99; p= 0.004), preeclampsia (AOR= 5.09, 95 % CI= 2.09 to 12.47; p <0.001). Conclusion: Birth asphyxia was found in 10.6 % of neonates. Birth asphyxia was significantly predicted by the mother’s educational level, complicated labor, and low birth weight. Keywords: proportion, Birth asphyxia, Newborns, Addis Ababa. Correspondence: Yohannes Godie. Debre Markos University, Ethiopia, Email: yohannesguadie@gmail.com, Mobile: +25192857735.